2021
DOI: 10.1177/21582440211040810
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Computer and Internet at Home on Academic Results of the Saber 11 National Exam in Colombia

Abstract: The use of a computer and internet connection allows high school and university students to access more relevant information. However, there is no consensus on the effects of the use of these tools on academic results. This work evaluates the impact of computers and the internet at home on the results of the Saber 11 test, a national exam taken by all students finishing their secondary education in Colombia, between 2017 and 2019. This impact was estimated from a pooled two-stage least squares (pooled 2SLS) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
1
2
0
3
Order By: Relevance
“…A literature review shows that studies in developed and developing countries produce similar outcomes. For example, Aguirre et al ( 2021 ) found evidence that computers and the internet at home positively impacted English language performance in Columbia. Sanchis-Guarner et al ( 2021 ) found that increasing broadband speed by 1Mbps increases test scores by 1.37 percentiles ranks in the UK.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review shows that studies in developed and developing countries produce similar outcomes. For example, Aguirre et al ( 2021 ) found evidence that computers and the internet at home positively impacted English language performance in Columbia. Sanchis-Guarner et al ( 2021 ) found that increasing broadband speed by 1Mbps increases test scores by 1.37 percentiles ranks in the UK.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the proliferation of the literature on the effect of technology on educational attainment or learning worldwide with mixed results (e.g., Aguirre et al, 2021 ; Sanchis-Guarner et al, 2021 ; Dettling et al, 2018 ; Fairlie et al, 2010 ; Harter & Harter, 2004 ; Cairlie & Robinson 2013 ), there is little empirical work in the context of COVID-19 pandemic. The present study contributes to the sparse literature on the effect of technology access on student learning hours, focusing on the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…En los resultados también inciden la edad (Celemín-Mora & Flórez-Romero, 2018;Timarán-Pereira et al, 2019;Barrios et al, 2021), el sexo (Arias-Velandia et al, 2018), el lugar de procedencia (Castro et al, 2018), la discapacidad (Celemín-Mora y Flórez-Romero, 2018), los estilos de aprendizaje (J. González et al, 2017;Redondo, 2018), lo motivacional (Dueñas et al, 2018), lo cultural y psicológico (Blanco & Chacón, 2020) y las funciones ejecutivas de atención y memoria (Amaya et al, 2020).…”
Section: Características Personalesunclassified
“…Así mismo, los resultados también se ven afectados por los ingresos económicos de las familias (Rozo, 2017;Palacios, 2020;Romero et al, 2021), el departamento de residencia (Romero et al, 2021) y el municipio (Castro et al, 2018), el barrio (Rozo Alzate, 2017), el estrato (Celemín-Mora & Flórez-Romero, 2018;Dueñas et al, 2018;Timarán-Pereira et al, 2019); el acceso de los estudiantes a un computador, a las TIC y al internet (Cerquera et al, 2018;Timarán-Pereira et al, 2019) y el uso que se les dé (Barrios et al, 2021).…”
Section: Características Socioeconómicasunclassified
See 1 more Smart Citation